Metabolomics in the developmental origins of obesity and its cardiometabolic consequences. (29th January 2015) - Hivert, M. F.; Perng, W.; Watkins, S. M.; Newgard, C. S.; Kenny, L. C.; Kristal, B. S.; Patti, M. E.; Isganaitis, E.; DeMeo, D. L.; Oken, E.; Gillman, M. W.
Abstract : In this review, we discuss the potential role of metabolomics to enhance understanding of obesity-related developmental origins of health and disease (DOHaD). We first provide an overview of common techniques and analytical approaches to help interested investigators dive into this relatively novel field. Next, we describe how metabolomics may capture exposures that are notoriously difficult to quantify, and help to further refine phenotypes associated with excess adiposity and related metabolic sequelae over the life course. Together, these data can ultimately help to elucidate mechanisms that underlie fetal metabolic programming. Finally, we review current gaps in knowledge and identify areas where the field of metabolomics is likely to provide insights into mechanisms linked to DOHaD in human populations.